Problem Solving Ability of Junior High School Students Through the Application of Problem Based Learning Model on Simple Aircraft Material Seen from Gender Differences - Putri Ameliasari; Insih Wilujeng (Postgraduate, University of Mataram, 2023)
The purpose of the study was to describe the profile of students' problem-solving skills through the application of problem-based learning models in terms of gender differences. This type of research is descriptive qualitative research. The research population was students of class VIII A SMPN 19 Bengkulu Selatan. The research instrument used was a problem-solving skills test. The data collection technique used a test in the form of a description question. Data analysis techniques using descriptive statistics. The results showed that, the average of female students' completeness results increased by 72.5, and the average of male students' indicator completeness increased by 73.5 This shows that, male students' problem-solving skills are greater than female students. The average value of male students is 0.36, with a moderate category, and the average value of female students is 0.48, with a moderate category. This shows that there are differences in problem solving skills between male students and female students. The conclusion in this study is that female students' problem-solving skills are higher than male students.